Proton-conducting Micro-solid Oxide Fuel Cells with Improved Cathode Reactions by a Nanoscale Thin Film Gadolinium-doped Ceria Interlayer - Li, Yong (2017)
An 8 nm-thick gadolinium-doped ceria (GDC) layer was inserted as a cathodic interlayer between the nanoscale proton-conducting yttrium-doped barium zirconate (BZY) electrolyte and the porous platinum cathode of a micro-solid oxide fuel cell (μ-SOFC), which has effectively improved the cathode reaction kinetics and rendered high cell power density. The addition of the GDC interlayer significantly reduced the cathodic activation loss and increased the peak power density of the μ-SOFC by 33% at 400 °C. The peak power density reached 445 mW/cm2 at 425 °C, which is the highest among the reported μ-SOFCs using proton-conducting electrolytes. The impressive performance was attributed to the mixed protonic and oxygen ionic conducting properties of the nano-granular GDC, and also to the high densities of grain boundaries and lattice defects in GDC interlayer that favored the oxygen incorporation and transportation during the oxygen reduction reaction (ORR) and the water evolution reaction at cathode.